The politics of reconciliation in New Zealand - Sullivan, Ann (Political Science, 2016)
Reconciliation in New Zealand involves recognition, reparations and an apology for past injustices relating to breaches of the Treaty of Waitangi. In 1840, Māori and the British Crown signed a treaty that promised a beneficial relationship to both signatories. Almost immediately after the Treaty was signed and continuing through to today, promises inherent in the principles of the Treaty have been breached. However, in 1975, a government-appointed permanent commission of inquiry was established to investigate actions or omissions of the Crown that breach the promises made in the Treaty of Waitangi. The Waitangi Tribunal and the Ministry of Justice provide the institutional mechanisms used in New Zealand to foster reconciliation. This article will discuss how the state has moved iwi from being in Treaty ‘grievance mode’ to one of tino rangatiratanga/Māori self-determination and demonstrates how reconciliation has integrated Treaty settlement iwi into the mainstream New Zealand economy.
Keywords: Indigenous rights; Māori; politics; reconciliation; treaty

Reconciliation: The Political Theological Nexus in Australasian Indigenous Public Policy - O’Sullivan, Dominic (International Journal of Public Theology, 2010)
Reconciliation brings together Christological and anthropological dimensions of human thought to illustrate the nexus between religious principles and political means. For the state reconciliation is concerned with social cohesion and political stability. For the church, it extends the sacramental notion of reconciliation between God and penitent to public relationships. This article examines Roman Catholic contributions to secular reconciliation debates. It shows how religious precepts create moral imperatives to engagement with secular discourses as a necessary element of Christian mission. It also argues that the church’s role in the disruption of indigenous societies creates an additional moral imperative to engage in reconciliation as mission and to articulate a Christian vision of indigenous rights.
Keywords: christianity; kāwanatanga; open access version available; reconciliation; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty settlements

Reconciliation as Public Theology: Christian Thought in Comparative Indigenous Politics - O’Sullivan, Dominic (International Journal of Public Theology, 2014)
Abstract Christian public theology extends reconciliation beyond its principal sacramental concern for relationships between God and penitent to the construction of ‘socially just’ public relationships for the settlement of intra-national conflict. In theological terms, reconciliation brings public relationships into what Hally calls ‘the Christ narrative of passion, death and resurrection’ in which the perpetrators of injustice repent and seek forgiveness. This article introduces the conflicts that these discourses aim to resolve in Australia, Fiji and New Zealand and explains and contrasts reconciliation’s relative importance in each of these jurisdictions. Moreover, the article’s cross-jurisdictional comparison shows reconciliation’s limits and possibilities as public theology, and argues that in Australia and New Zealand it has helped to create political environments willing to admit indigenous perspectives on a range of policy issues. On the contrary, however, the article also shows that the Fijian churches have distorted the concept of reconciliation to support political imperatives that are difficult to rationalize theologically, even though they are presented by the churches as being concerned with religious goals.
Keywords: christianity; colonisation; kāwanatanga; reconciliation; religion